2023
DOI: 10.46382/mjbas.2023.7104
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Short-Form Video Advertising on Social Media on the Purchase Intention of Gen Z in Vietnam

Abstract: In recent years, short-form video has become a popular form of advertising on social media. The way consumers make decisions to purchase has changed owing to this new marketing method. This study aims to investigate the impact of informativeness, entertainment, credibility, social interaction, incentives and irritation of short-form video advertising on social media on the purchase intention of Gen Z in Vietnam through user attitude and advertising value. A survey was conducted by collecting responses from 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Factors like interactivity, credibility, and incentives highly influence customers' purchase intentions and behavior (Tuan et al, 2023).…”
Section: Maintaining the Integrity Of The Specificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors like interactivity, credibility, and incentives highly influence customers' purchase intentions and behavior (Tuan et al, 2023).…”
Section: Maintaining the Integrity Of The Specificationsmentioning
confidence: 99%
“…SMEs that are less known can utilize this, especially SMEs with categories relating to fashion, beauty, dining and travel offers. In addition to this, studies have shown that short-form video advertising has been the most effective at enhancing overall use engagement, lengthening visits, boosting commerce, boosting traffic, and lowering support inquiries (Tuan et al, 2023). SMEs can utilize this by using Facebook reels, which allow you to share videos up to 90 seconds long.…”
Section: Facebook Marketing As a Marketing Tool In Vietnammentioning
confidence: 99%
“…Short-form video is commonly defined as any type of video content with a duration within five minutes [1]. The media type first surfaced around 2012 and is commonly credited to social media platforms Snapchat and Vine.…”
Section: Background Informationmentioning
confidence: 99%
“…The rise of social media and short-form media prompted the creation of a new business model for small-to-medium-sized businesses called Social commerce [4], named for its reliance on social and short-form media advertisements. These advertisements commonly feature an amateur-esque video aesthetic to fit in with other user-created content and create the perception of customer word-of-mouth for increased relatability [1]. The objective of this was to decrease the distinction between advertisements and content so that ads would have a stronger earned media attraction, thanks to the consumer tendency to value peer reviews over company advocacy [3].…”
Section: Background Informationmentioning
confidence: 99%